2011
DOI: 10.1093/ecam/neq059
|View full text |Cite
|
Sign up to set email alerts
|

Role of Apoptotic Proteins in REC‐2006 Mediated Radiation Protection in Hepatoma Cell Lines

Abstract: The present study was carried out to evaluate the role of apoptotic proteins in REC-2006-mediated radiation protection in hepatoma cell lines. REC-2006 treatment 2 h before irradiation strongly inhibited the cleavage of ATM and PARP-1 in HepG2 cells. The expression of nuclear apoptosis inducing factor (AIF) was found to be more inhibited (~17%) in HepG2 cells in REC-2006 + radiation-treated group. More inhibition (~33%) of cytochrome c was observed in HepG2 cells upon REC-2006 treatment 2 h prior irradiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…HepG2 (wtp53, carrying wild-type p53), Hep3B (p53 null, lacking p53) and MHCC97L (mutp53, harboring mutant p53) human hepatoma cell lines [28], [29] were obtained from the Cell Institute of Shanghai (Academia Sinica, Shanghai, China). Cells were maintained at 37°C in a humidified incubator under 5% CO 2 and grown in Dulbecco’s modified Eagle medium (DMEM) supplemented with 10% fetal bovine serum, 50 mg/ml penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…HepG2 (wtp53, carrying wild-type p53), Hep3B (p53 null, lacking p53) and MHCC97L (mutp53, harboring mutant p53) human hepatoma cell lines [28], [29] were obtained from the Cell Institute of Shanghai (Academia Sinica, Shanghai, China). Cells were maintained at 37°C in a humidified incubator under 5% CO 2 and grown in Dulbecco’s modified Eagle medium (DMEM) supplemented with 10% fetal bovine serum, 50 mg/ml penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Our earlier studies of Podophyllum hexandrum were predominantly focused on the radioprotective efficacy of its whole or semi‐purified extracts in mouse models and in various cell lines [Shukla et al, ; Gupta et al, ; Singh et al, ]. In contrast, the current study examines the efficacy of a new formulation, termed G‐002M, generated by combining just three active compounds extracted from Podophyllum hexandrum (G‐002M).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the affects of SQGD on modulation of radiation‐induced apoptosis, cell cycle perturbations and DNA damage, protein expression analysis was carried out. Previous studies have established the role of functional P53 protein in the cell cycle regulation and apoptosis induction (Burger et al, ; Wilson et al, ; Kumar et al, ; Singh et.al., ) under various kinds of stresses. In the current study, high level of P53 expression was observed in the mice treated with SQGD before irradiation at 24 h compared with untreated control; however, expression levels of P53 was found to be remained at lower side at all tested time points when compared with the irradiated mice [Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the radiation‐induced damage, several drugs and formulations such as amifostine (Andrieu et al, ), cysteamine, MPG (Routh et al, ), LPS, and CBLB 502 (Burdelya et al, ) of natural and chemical origin have been evaluated for their radioprotective efficacy in vitro and in vivo models. Several natural plant extracts such as Podophyllum hexandrum, Rhodiola, Hippophae rhamnoides, Tinospora cordifolia, Ocimum sanctum, Psoralea corylifolia (Arora et al, ; Kumar,et al, b; Chawla et al, ; Singh et al, b; Chawla et al, ; Singh et al, ; Sharma et al, ), and so on have also been studied for their radioprotective activities. However, due to associated toxicity along with their efficacious doses, search for nontoxic or relatively less toxic radioprotective agents is continued.…”
Section: Introductionmentioning
confidence: 99%